Theory of Mind in migraine and medication-overuse headache: A cross-sectional study - Romozzi, Marina; Di Tella, Sonia; Rollo, Eleonora; Quintieri, Paolo; Silveri, Maria Caterina; Vollono, Catello; Calabresi, Paolo (Frontiers in Neurology, 2022)
Background: Theory of Mind (ToM) is the ability to predict and anticipate others’ behaviors through the mental state attribution process. This study aims to investigate the ToM in patients with medication overuse headache (MOH) and episodic migraine (EM) and to compare it with healthy controls (HC). Methods: This study enrolled patients with MOH, patients with EM and HC. ToM was assessed through the Theory of Mind Assessment Scale (ThOMAS), which includes four subscales: Scale A, I-Me, Scale B, Other-Self, Scale C, I-Other, Scale D, Other-Me, through the Reading the Mind in the Eyes test (RMET), which measures complex emotion recognition and, through the Toronto Alexithymia Scale (TAS-20) which measures alexithymia. Concomitant psychiatric disturbances were evaluated through the Hamilton Anxiety Rating Scale, the Hamilton Rating Scale for Depression, and the Dissociative Experiences Scale-II. Results: The study involved 21 patients with EM, 22 patients with MOH, and 18 HC. In all the four subscales of the ThOMAS, there was a significant difference between HC, EM, and MOH patients: Scale A (p=0.009), Scale B (p=0.004), Scale C (p=0.039), and Scale D (p=0.008). In the RMET, MOH patients had worse performances than EM patients and HC (p=0.039). MOH group exhibited higher levels of alexithymia when compared to the HC (p=0.033) and higher levels of anxiety than HC (p=0.001). Conclusion: MOH patients showed a subtle psychopathological pattern characterized by impaired social adaptation.